Censorship detected in VN (Vietnam) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Vietnam. Data sourced from OONI.
Censorship Incident ID: VN-2026-0926. Severity: critical. Confidence: 84%